Masking in the modulation rate domain - Lemańska, J.; Sęk, A. P.; Rybicka, W. (Archives of Acoustics, 2003)
This study examines the amplitude modulation (AM) detection in the presence of a masking modulating signal. The detection thresholds of sinusoidal amplitude modulation were measured for a 4 kHz sinusoidal carrier. The masking modulators were a 16 Hz tone, a bandwidth of a low-noise noise centered at 16 Hz with a bandwidth of 2 or 8 Hz, and the gaussian noise centered at 16 Hz with a 8 Hz bandwidth. A 3AFC procedure was used. The results obtained suggest the existence of a masking effect in the modulation rate domain. This form of masking is the most effective one when the modulation frequency of the masking signal is close to the masker or, in the spectral range of masking, to the modulation signal. These results are consistent with experimental data, which suggest the existence of frequency selectivity and tuning in the amplitude modulation domain. The results obtained are consistent with the idea of a second stage of filtering in the auditory system by means of so-called modulation filters. It seems that the auditory system performs a limited resolution spectral analysis of the signal amplitude envelope. However, it is necessary to stress that the frequency selectivity in the amplitude modulation domain is not so evident as the selectivity in the audio frequency domain.